PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMP SEMEN PADANG - Suci, Sari Febria; Mukhni, Mukhni; Yunita, Alfi (STKIP PGRI Sumbar, 2013)
The background of this research is the low of the studentâs understanding of mathematical concepts, so that most of the studentâs get the score under Criteria Minimum Masteri (KKM),Â the students do not active a long the learning process. The purpose of this research is to sint out the studentâs learning activiti a long the application of kooperatif learning type Talking Stick and to now that the studentâs understanding mathematical concept by using learning Talking Stick strategi more better than the studentâsÂ understanding of mathematical concepts by using conventional learning in class IX of SMP Semen Padang. The study of this research is experimental, by design random experiment to ward tha subject. The population of this study is studentâs of class IXSMP Semen Padang that consist of five classes. The sampel take by using random sampling tecnique.The instrument of this research is the observation paper of studentâs activities and the test of understanding mathematical concept. The technique of analyzing data of this research is T-test one hide by MINITAB. So that researcer can conclude that It the students understanding of mathematical concepts by using kooperatif learning type talking stick better than students with an understanding of the mathematical concept learning in class IX conventional SMP Semen Padang.Keywords:kooperatif Learning, Class Concern, Understanding Concepts